Association between baseline serum vascular endothelial growth factor levels and response to electroconvulsive therapy. (20th August 2013) - Minelli, A.; Maffioletti, E.; Bortolomasi, M.; Conca, A.; Zanardini, R.; Rillosi, L.; Abate, M.; Giacopuzzi, M.; Maina, G.; Gennarelli, M.; Bocchio‐Chiavetto, L.
<x xml:space="preserve">Abstract</x> Objective Several studies have shown that vascular endothelial growth factor (VEGF) is implicated in different neuronal processes involved in major depressive disorder (MDD) and in the mechanisms of action of antidepressants. The aim of this study was to investigate whether VEGF serum levels before treatment might be associated with the antidepressant response. Method Two groups of patients were enrolled. One was composed of 50 MDD patients receiving an antidepressant drug treatment. Illness severity was measured before the treatment (T0) and after 12 weeks (T1). The second group was composed of 67 treatment‐resistant depressed (TRD) patients undergoing electroconvulsive therapy (ECT). Illness severity was assessed before the treatment (T0) and 1 month after the end of ECT (T1). Blood samples for VEGF measurements were collected for both groups at the baseline (T0). Results A significant correlation was observed between baseline VEGF serum levels and the percentage reduction in depressive symptomatology after ECT (P = 0.003). In particular, VEGF levels at baseline were significantly lower in patients showing no response to ECT at follow‐up (P = 0.008). No correlation between T0 VEGF concentrations and drug treatment outcome was found. Conclusion Our results suggest that VEGF plays a role in the mechanism of response to ECT.